Genetic mapping of the A. nidulans xprE gene - M. E. Katz (Fungal Genetics Reports, 1996)
Strains carrying the xprE1 mutation produce very little or no extracellular proteases in response to carbon and nitrogen limitation and have reduced levels of extracellular protease in response to sulphur limitation. Haploidization analysis has shown that the xprE gene is located on A. nidulans chromosome VI (Katz et al. 1996, Mol. Gen. Genet., in press). In order to isolate the xprE gene using the A. nidulans physical map a more accurate position of the gene has now been determined. The gene order on chromosome VI is lysA, xprE, sB, sbA .